Polymeric solar cells : materials, design, manufacture - Krebs, Frederik C. (Destech Publications, 2010)
Book offers a comprehensive treatment of nonhybrid polymeric solar cells from the basic chemistry of donor and acceptor materials through device design, processing and manufacture. Written by a team of Europe-based experts, the text shows the steps and strategies of successfully moving from the science of solar cells to commercial device production. Chapters focus on technologies that lead to increased efficiencies, longer usable life and lower costs. Highlighted are ways to fabricate solar cells from a range of polymers and develop them into marketable commodities. Special consideration is given to solar cells as intellectual property.